Atypical presentation of acute coronary syndrome (ACS): a case report. Issue 6 (2nd November 2018) - Van Damme, Axel; Vanderheeren, Philippe; De Backer, Tine; Desimpel, Françine
Abstract: Case: A 45-year-old man presented at the emergency department (ED) with stomach pain since eight days. The patient was not worried about his symptoms and requested only pain relief. The emergency physician requested a consult of the gastroenterologist. Clinical examination was unremarkable. However, 12-lead ECG and ischemic markers were suggestive of acute coronary syndrome (ACS) which led to admission at the cardiology department. Despite delayed presentation, the patient was still referred for urgent coronary angiogram after receiving heparin, ticagrelor and acetylsalicylic acid because of persistent pain. An acute occlusion of the posterior descending artery was visualized and a percutaneous coronary intervention (PCI) with implantation of a drug-eluting stent was performed. Discussion: Atypical presentation of ACS can range from non-chest pain to an epileptic seizure. Risk factors for atypical presentation include female gender, old age, comorbidities and severe mental illness. Troponin testing plays a central role when confronted with ACS but has only limited added-value with non-chest pain ACS. In cohort studies 1–2.2% of diagnosis of ACS is missed by emergency physicians. Possible explanations include atypical symptoms, non-diagnostic ECG and failure to interpret subtle ECG changes. ACS without chest pain frequently gets underdiagnosed and undertreated, which leads to more complications and a higher in-hospital mortality rate.